Racing the Light - Crais, Robert (New York : G. P. Putnam's Sons, 2022)
"Private investigator Elvis Cole and his enigmatic partner Joe Pike are back on the case in this brilliant new thriller from #1 New York Times bestselling author Robert Crais"--
Keywords: Cole, Elvis (Fictitious character) -- Fiction; Private investigators -- Fiction. -- California; Cole, Elvis (Fictitious character) -- Fiction; Private investigators -- Fiction; Detective and mystery stories; Mystery fiction; Detective and mystery fiction; Thrillers (Fiction)